(untitled) (Research, Society and Development, 2023)
The article addresses the importance of extensometry in evaluating cabling conditions in structural projects and analyses. The need for a more elaborate assessment of the existing forces is highlighted to avoid failures due to overload or wear during the useful life of the parts. In a competitive market that demands cost and quality reduction, extensometry emerges as a fundamental technique. Extensometry is presented as an experimental technique for analyzing stress and deformation in mechanical and masonry structures. However, in practice, the extensometer is described as a sensor glued to the surface of the object of study, capable of measuring deformations and, therefore, so complex. The change in the electrical parameter, usually resistance, results in a variation in current, whose values are interpreted by a data acquisition board and computational tool. The objective of the work is to find the modulus of elasticity and the initial deformation relationship and linear regression of the fibrous composite used, when subjected to loads, such analysis carried out using the extensometer. However, the behavior of the composite is analyzed in the form of increasing and then decreasing load addition. However, using the data obtained, a linear regression of the graph curve is performed. The text highlights the peculiarities of strain gauges, which are used to measure several variables, such as load, tension, stretching, variation and vibration. In this context, the analyzes carried out in the work had positive results, managing to find the elastic modulus of the composite through equations and graphs.